2021
DOI: 10.1186/s12953-021-00177-9
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based proteomic analysis of sperm reveals candidate proteins that affect the quality of spermatozoa from boars on plateaus

Abstract: Background Tibetan pigs (TP) exhibit heritable adaptations to their hypoxic environments as a result of natural selection. However, candidate proteins that affect the sperm quality of boars on plateaus have not yet been clearly investigated. Methods In this study, to reveal the candidate proteins that affect the quality of spermatozoa of boars on plateaus, we analyzed the sperm quality using computer-assisted semen analysis (CASA) system and reacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Proteomics has also enabled the identification of candidate protein markers of fertility for molecular breeding. The LC-MS/ MS analysis of pig sperm revealed eight fertility-related proteins over-represented in Tibetan pigs having heritable adaptation to hypoxic environments (Zhao et al, 2021). In another study, analysis of seminal plasma proteins by LC-MS/MS found a consistent correlation of 1,343 proteins with fertility (Willforss et al, 2021).…”
Section: Proteomicsmentioning
confidence: 94%
See 1 more Smart Citation
“…Proteomics has also enabled the identification of candidate protein markers of fertility for molecular breeding. The LC-MS/ MS analysis of pig sperm revealed eight fertility-related proteins over-represented in Tibetan pigs having heritable adaptation to hypoxic environments (Zhao et al, 2021). In another study, analysis of seminal plasma proteins by LC-MS/MS found a consistent correlation of 1,343 proteins with fertility (Willforss et al, 2021).…”
Section: Proteomicsmentioning
confidence: 94%
“…However, the application of proteomics in livestock research has been limited in the past due to its high cost and lack of optimized protocols for various cell types in different species (Baykalir et al, 2018). Nevertheless, with advancements in new analytical methods and computational tools for the analysis of proteomic data, reports on proteomics studies in animal science are increasing for understanding the animal health status and production and reproduction efficiency (Zhao et al, 2021;Kaya et al, 2022;Ye et al, 2022).…”
Section: Proteomicsmentioning
confidence: 99%
“…The lysate was centrifuged at 12,000× g for 5 min at 4 °C to obtain the supernatant. G250 staining solution (detergent compatibility, 300 µL) was added to the sample (10 µL), the absorbance was measured at 595 nm, and the protein concentration was obtained according to the standard curve [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…3A, P < 0.05). Also, VDAC2, ENO1, and GPX4 proteins were used as the spermatogenesis markers [36][37][38] which was uniquely clustered in fertility related transcriptomes from bovine spermatozoa (Fig. 1B).…”
Section: Differential Fertility-related Protein Level In Bovine and P...mentioning
confidence: 99%